Effect of eye rubbing on corneal biomechanical properties in myopia and emmetropia - Li, Xia; Wei, Anji; Yang, Yujing; Hong, Jiaxu; Xu, Jianjiang (Frontiers in Bioengineering and Biotechnology, 2023)
Purpose: To investigate short-term changes in corneal biomechanical properties caused by eye rubbing in myopia and emmetropia and compare the different responses between the two groups. Methods: This was a prospective observational study of 57 eyes of 57 healthy subjects aged 45 years and younger. The participants were divided into myopia and emmetropia groups. All the subjects underwent eye rubbing by the same investigator using the same technique. Biomechanical parameters were recorded using the Corvis ST device before and after 1 min of eye rubbing. One week later, all the participants underwent the test again. Statistical methods were employed to compare the differences between the data from before and after the 1 min of eye rubbing and demonstrate the different responses of the two groups. Results: After 1 min of eye rubbing, smaller SP-A1 (p < 0.001), higher deformation and deflection amplitudes (p < 0.001, p = 0.012), higher peak distances (p < 0.001), earlier A1 times (p < 0.001), faster velocities (p < 0.001), and lower maximum inverse radii (p = 0.004) were observed. According to the automatic linear modeling analysis, the refractive states (B = −5.236, p = 0.010) and biomechanically corrected intraocular pressure (bIOP) (B = 0.196, p = 0.016) had influenced a decrease in the stiffness parameter at the first applanation (SP-A1). The central corneal thickness (CCT) had decreased only in the myopia group (p = 0.039). The change of SP-A1 in amplitude was larger in the myopia group than in the emmetropia group (p < 0.001). All the parameters returned to the baseline level 1 week later. Conclusion: Eye rubbing appears to alter corneal biomechanical properties temporarily and make the cornea softer, especially for myopic young patients.